Hygiene and Immunity: Strengthening Immunity through Proper Hygiene - Rashidova Mukhlisa Yorqin qizi (Journal of Science in Medicine and Life, 2024)
In the Western world, the incidence of infectious diseases has decreased dramatically due to improved hygiene, vaccines, and antibiotics. We have become too dependent on pharmaceuticals, forgetting the need to strengthen the immune system. We were reminded of this by the recent outbreak, which particularly affected vulnerable groups with weakened immune systems. In addition, it turned out that the intestines play a more complex and important role than previously thought. It goes beyond digestion, which is the primary function of the intestines, and affects every system in the body. The gut microbiota is important, established at birth, and closely related to the immune system through complex digestive and metabolic functions. Intestinal microbiota together with intestinal epithelial cells form a protective barrier against pathogens, play an active role in the formation and functioning of the immune system, activate anti-inflammatory mechanisms and stop inflammatory mechanisms.